Tingkat Kecanduan Internet pada Remaja Awal - Ayu Permata Sari; Asmidir Ilyas; Ifdil Ifdil (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2017)
This study shows that there are students who have an Internet addiction. Addictions possessed by students will certainly have a negative impact on self, social relationships and learning outcomes. This study aims to describe: 1) The level of Internet addiction in general 2) The core symptoms of Internet addiction in early adolescents 3) Problems related to Internet addiction in early adolescence. Quantitative research method with the quantitative descriptive approach. The population of this study is 596 students of SMA N 7 Padang and a sample of 240 students selected by proportional random sampling technique. The results revealed: 1) The rate of internet addiction in early adolescence is generally mostly in the moderate category with a percentage of 50%, 2) The core symptoms of Internet addiction in early adolescence are mostly in the high category with a percentage of 43%, consisting of indicators of compulsive symptoms, withdrawal symptoms and tolerance symptoms. 3) Internet-related addiction problems in early adolescence were mostly in the moderate category with a 49% percentage consisting of two interpersonal indicators & health problems and time management problems.